Modulation of Cell Proliferation Pathways by the Hepatitis B Virus X Protein: A Potential Contributor to the Development of Hepatocellular Carcinoma - Casciano, Jessica C.; Bagga, Sumedha; Yang, Bei; Bouchard, Michael J. (IntechOpen, 2012)
None